Current progress of biopolymer-based flame retardant - Mohammad Taib, Mohamad Nurul Azman; Antov, Petar; Savov, Viktor; Fatriasari, Widya; Madyaratri, Elvara Windra; Wirawan, Riza; Osvaldov´a, Linda Makovick´a; Lee, Seng Hua; Abd Ghani, Muhammad Aizat; Osman Al Edrus, Syeed Saifulazry; Lum, Wei Chen; Trache, Djalal; et al. (Elsevier, 2022)
Due to thermal and flame/fire sensitivity of biopolymers especially in plant-based biopolymer fillers, it is extremely and necessary to improve the reaction to flame. The bio-polymers currently are used in many applications and daily life products and due to the potential risks of its tendency to burn and widespread the flames. To overcome these risks, an introduction of flame retardant (FR) compounds, additives, or fillers based on organic and inorganic approaches such as nitrogen-based FRs, halogenated-based FRs, and nano fillers have becoming significant incorporated into biopolymers. Most traditional uses of FRs that involve halogenated and inorganic FRs are toxic and non-biodegradable during disposal. Thus, the need to look for more environmentally friendly FRs such as nanocellulose, lignin, and others have become crucial. Because of concern on environmental and human health issues the biopolymers becoming a popular subject nowadays among scientists and researchers. The aim of this review paper is to promote the use of biodegradable and bio-based compounds for flame retardants with reduction in carbon footprint and emission. Furthermore, the addition of bio-based FRs are significant in preventing and reducing the spread of flames compared with conventional FRs. A detailed discussion on the flame retardants mechanism, characterization techniques, morphology correlation and various biopolymers with flame retardants are also discussed.